The study of structural effect on export competitiveness in Malaysian electrical and electronic (E&E) sector / Haslina Che Yaacob, Dr. Nik Maheran Nik Muhammad and Zurina Ismail - Che Yaacob, Haslina; Nik Muhammad, Nik Maheran; Ismail, Zurina (Institute of Research, Development and Commercialization (IRDC), 2007)
Malaysia is among the world's top 20 trading nations. This is due to the structural change in the Malaysian economy that turned the country from an exporter of primary commodities into an exporter of high value-added manufactured products. In Malaysia, E&E forged a strong foundation over the 1 ast 3 decades, which provides new opportunities for such investments. This study analyses the structural effect on export competitiveness of Malaysian E&E products focusing on semiconductor (SITC 776), Telecommunication product (SITC 764), Electrical machinery, Apparatus, Part and necessary (SITC 772), Printed Circuit Board (SITC 759) and Disk drives, printers and PCs (SITC 752). Furthermore, the study uses the Constant market share (CMS) and revealed comparative advantage (RCA) framework to analyze the extent of the export competition between Malaysia and other competitor economies. Overall, CMS result shows that in the first sub-period (1990-1994), Malaysia E&E export was competitive in the four markets studied, namely USA, Singapore, Japan and Hong Kong. However, in the second and third period, CMS result shows that Malaysia E&E export increased but not due to market competitiveness but due to the structural effect - that is due to an increased in the world import. In terms of export performance ratio, RCA results show that, Malaysia E&E product only performed was highly in the US market for almost all SITC. Indonesia has concurred the Singapore market and Hong Kong was concurred by China. However, Malaysia E&E export to the world generally has comparative advantage over other competitors namely Indonesia, Thailand and China. The study also revealed that Malaysia has higher export capacity to other countries besides USA, Singapore, Japan and Hong Kong. Therefore the argument saying that China will intensify the competitiveness of Malaysian E&E market is questionable since the study cannot reveal the comparative advantage hold by China. The study found that China only dominated the Hong Kong Market for almost all SITC studied.